Investigation on stability and performance of a free-piston Stirling engine - Kwankaomeng, Sutapat; Silpsakoolsook, Banterng; Savangvong, Pongnarin (My University, 2014)
The stable operation of a free-piston Stirling engine will be achieved when both engine configurations and operating conditions are optimum. This paper presents stability and performance investigation of free-piston Stirling engine. Isothermal analysis is considered in the simulation. Dynamic motion of engine pistons such as the displacer and the power piston are both obtained. For engine design, the optimum parameters are given such as engine specifications, engine characteristics and working conditions to yield the maximum efficiency and reliability. The prototype was built and tested. The comparison of both experimental and simulation results are provided and discussed. 1876-6102© 2014 Published by Elsevier Ltd.
Keywords: Dynamic; Free-piston Stirling engine; Isothermal; Optimum; Stirling engine